Analisis Manajemen Produksi Pada Mebel Sekawan Rimba Desa Wangkal Kecamatan Gading Kabupaten Probolingo - Ahmad Jufri; Fahrudin F (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Production management can be defined as a process that continuously and effectively uses management functions to efficiently integrate various resources in order to achieve company goals. This study aims to analyze the production management of Sekawan Rimba's furniture business and to determine the supporting and inhibiting factors for the production management of Sekawan Rimba's furniture business. This study uses a qualitative method of descriptive analysis approach. Data collection techniques were carried out by observation, interviews, and documentation. The data validation techniques used method and source triangulation, by collecting similar data and information from a variety of different sources. Data analysis in this study used an interactive model, namely a four-stage collection analysis: consisting of data collection, data presentation, data reduction, and verification/conclusion. The results of the study show that Sekawan Rimba furniture has carried out the operational management function properly so that it is able to maintain its business existence. By using good raw materials and having an experienced workforce, Sekawan Rimba furniture is able to produce quality products and consistently produce their products. Quality products and friendly service can satisfy consumers. One of the obstacles in the production process at Sekawan Rimba furniture is that there are only a few skilled workers, so other workers need to get more direction. And labor indiscipline in terms of delivery of goods which are often late.